LIMA (v2.0): A full two-moment cloud microphysical scheme for the mesoscale non-hydrostatic model Meso-NH v5-6 - M. Taufour; J.-P. Pinty; C. Barthe; B. Vié; C. Wang (Geoscientific Model Development)
A full two-moment microphysics parameterization of the LIMA scheme (with LIMA standing for Liquid Ice Multiple Aerosols and hereafter named LIMA v2.0) has been developed and successfully implemented in the Meso-NH cloud-resolving model. The novelty of the scheme is a set of prognostic equations of the number concentration of each precipitating ice category (snow/aggregates, graupel, and hail), in addition to the prediction of the mass mixing ratios. As a result, new microphysical conversion rates are introduced and explicitly computed using the size distributions of the hydrometeors.